When freedom bleeds : journey through Indian emergency - Toofan, Brij Mohan, 1920- (Delhi : Ajanta Publications : Distributed by Ajanta Books International, 1988)
Reminiscences and diary, 1975-1976, by a political activist.
Autobiographical.
Keywords: Toofan, Brij Mohan, -- 1920- -- Diaries; Politicians -- India -- Diaries; India -- Politics and government -- 1975-1977.